A scoping review to understand “leadership” in interprofessional education and practice - Brewer, Margo; Flavell, Helen; Trede, F.; Smith, M. (Informa Healthcare, 2016)
© 2016 Taylor & Francis This scoping study examined how “leadership” is referred to and used in interprofessional education and practice. A total of 114 refereed articles were reviewed to determine how leadership is defined, conceptualised, and theorised. The review also examined what capabilities were identified for effective interprofessional leadership. The majority of papers were empirical studies undertaken by researchers based in North America. The majority of articles did not refer to a specific leadership approach, nor did they define, describe, or theorise leadership. Moreover, “leadership” capabilities were rarely identified. Articles generally focused on health practitioners and educators or students as leaders with little exploration of leadership at higher levels (e.g. executive, accrediting bodies, government). This review indicates the need for a more critical examination of interprofessional leadership and the capabilities required to lead the changes required in both education and practice settings. The goal of this article is to stimulate discussion and more sophisticated, shared understandings of interprofessional leadership for the professions. Recommendations for future research are required in both education and practice settings.